Analisis Faktor Daya Saing, Budaya Keuangan, dan Keputusan Pembayaran Kredit terhadap Peluang Akses Layanan Keuangan UKM Lombok - Baiq Desthania Prathama (Universitas Sultan Ageng Tirtayasa, 2021)
Recent empirical studies have shown that access to finance is an obstacle for SMEs to grow. Seeing this condition, OJK has set regulations related to UKM online financing (equity crowdfunding), which is booming in the financial world. This study analyzes the effect of competitiveness, financial culture, and credit payment decisions on access to finance. Sampling is based on the type of business and the category of small and medium enterprises. Data was collected from distributing questionnaires to 171 SMEs in Lombok using a door to door approach and filling out assistance. The data were tested statistically for descriptive analysis, validity and reliability, and linear regression. The results showed that there was a positive influence of competitiveness, financial culture, and credit payment decisions on SMEs financial access. These findings demonstrate the importance of the competitiveness and financial culture of SMEs to access external finance. SMEs can increase the capacity and willingness of SMEs to apply for funding. The results of the study also contribute to literacy in the financial sector related to the accessibility of SMEs in financing and credit payment decisions, competitiveness, and financial culture